Analysis of the diversity and function of the alleles of the rice blast resistance genes Piz-t, Pita and Pik in 24 rice cultivars - Yan WANG; Jia-ming ZHAO; Li-xia ZHANG; Ping WANG; Shi-wei WANG; Hui WANG; Xiao-xi WANG; Zhi-heng LIU; Wen-jing ZHENG (Journal of Integrative Agriculture, 2016)
Understanding the sequence diversity of rice blast resistance genes is important for breeding new resistant rice cultivars against the rice blast fungus Magnaporthe oryzae. In this study, we selected 24 rice cultivars with different genetic backgrounds to study the allelic diversity of rice blast resistance genes Piz-t, Pita and Pik. For Piz-t, a total of 17 allelic types were found within the 24 cultivars. Blast inoculations showed that most of the mutations can affect the function of the resistance gene. For Pita, except for the difference at the 918th amino acid, a majority of the 21 mutations were detected among the cultivars. Inoculations with blast isolates carrying Avr-Pita revealed that cultivars with mutations in other sites except for the 918th amino acid did not affect the function of the Pita gene. For Pik, a total of six allelic types were found within the 24 cultivars, but five of them lost the function of the resistance gene. In addition, we found that Piz-t, Pita and Pik were expressed constitutively in the 24 rice cultivars and the expression level was not related to resistance. Our results have provided the sequence diversity information of the resistance genes Piz-t, Pita and Pik among the popular rice cultivars grown in the northeast region of China.